Responsibility to Rebuild: An Appraisal of the LLRC’s Recommendations Pertaining to Fostering Reconciliation in Waraffected Sri Lanka - Seneviratne, W. (My University, 2012)
Sovereignty is no more an absolute right of a State in the contemporary world. Sovereign States possess rights, as well as obligations. Due to this transformation and increased State practice, the international community expects certain behaviour from sovereign States. Accordingly, sovereign authorities are responsible for the safety and wellbeing of their citizens. When they do not provide necessary protection and assistance to affected communities in their countries, the international community increasingly makes interventions to remedy the situation. Since the legitimacy of such interventions is controversial and at times has caused further problems, the International Commission on Interventions and State Sovereignty (ICISS) introduced the ‘Responsibility to Protect’ concept to the world in 2001. Accordingly, sovereign States embrace three types of responsibilities for their citizens: responsibility to prevent, to react, and to rebuild. Under the notion of ‘responsibility to rebuild’, States are obliged to provide, particularly after an armed conflict, full assistance to their citizens with recovery, reconstruction and reconciliation, addressing the root causes of the harmful situation. If the obligations are not discharged by the State concerned, the international community gets involved to protect and assist the affected communities in such a State. At present, Sri Lanka is transforming from war to peace. The need of the hour is to respond effectively to challenges in sustainable communities. The Government of Sri Lanka (GOSL) attempts to foster reconciliation and to rebuild the war ravaged society. Since the end of the hostilities, the Government has taken several initiatives to achieve the above purposes. The main objective of this research paper is to examine and evaluate the most striking initiative taken by the GOSL pertaining to fostering reconciliation in the war-affected country: the Report of the Lessons Learnt and Reconciliation Commission (LLRC) from a legal point of view. Accordingly, the recommendations of the LLRC’s Report pertaining to reconciliation will be primarily appraised. The recommendations of the LLRC could draw the attention of a wide spectrum of audience locally and internationally. The most prominent observation has been the Resolution adopted by the United Nations Human Rights Council (UNHRC) in March 2012 pertaining to the promotion of the reconciliation and accountability in post-war Sri Lanka. The crux of the Resolution focused on the expeditious implementation of the constructive recommendations made in the LLRC’s Report and to take all necessary additional steps to fulfil the relevant legal obligations of the State in order to ensure accountability and reconciliation for all Sri Lankans. Although the GOSL opposed the adoption of this Resolution, the Government stated that it has already launched appropriate steps to foster reconciliation in the country.